Physical Fitness in Preschool Children - Mirosław Mrozkowiak; Alicja Kaiser (Kazimierz Wielki University, 2021)
Introduction. The level of mental and motor development as well as physical fitness and perceptual-motor performance should guarantee success in adapting to the new school environment. The aim of the research. The aim of the research was to determine physical fitness in preschool children of both genders aged from 4 to 7 years. Material and methods. The study included 275 children at the chronological age of 4 to 7 years including 134 girls and 141 boys. In order to assess physical fitness, the authors used the Wrocław Physical Fitness Test for preschool children completed by the endurance test Results. Final physical fitness results showed that six-year-old boys were the fittest and less fit were girls at the age of seven. The least fit were boys and girls at the age of four.        Conclusions The Wrocław Physical Fitness Test and the endurance test revealed that the experimental group of children aged between four and seven years from the Western Pomerania region represented a satisfactory physical fitness level. It should be noted that this level was significantly lower than the ones obtained in tests conducted by other authors in 2006, 1996, 1972, and 1967. The represented fitness level, especially the level of endurance, may result in adaptation disorders during the school shock period. The phenomenon of sexual dimorphism at preschool age is demonstrated by significantly better physical fitness in boys at the age of five and six and balanced fitness at the age of seven. Positive development of physical fitness is not supported by ongoing lifestyle pre-orientation. It is recommended to complete primary school admission criteria for the first form by physical fitness standards, including endurance.